2020
DOI: 10.1038/s12276-020-00534-2
|View full text |Cite
|
Sign up to set email alerts
|

Nuciferine modulates the gut microbiota and prevents obesity in high-fat diet-fed rats

Abstract: Gut microbiota dysbiosis has a significant role in the pathogenesis of metabolic diseases, including obesity. Nuciferine (NUC) is a main bioactive component in the lotus leaf that has been used as food in China since ancient times. Here, we examined whether the anti-obesity effects of NUC are related to modulations in the gut microbiota. Using an obese rat model fed a HFD for 8 weeks, we show that NUC supplementation of HFD rats prevents weight gain, reduces fat accumulation, and ameliorates lipid metabolic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 61 publications
(93 reference statements)
6
48
0
Order By: Relevance
“…The metabolic activity of the gut microbiota can be linked to host body energy homoeostasis by short-chain fatty acids (SCFAs), which are produced by gut microbiota catabolizing dietary fibers (Topping and Clifton, 2001). There is compelling evidence that nutrients can attenuate obesity by reprogramming gut microbiota (Xu et al, 2017;Yin et al, 2018;Zhang et al, 2019;Wang et al, 2020;Zhong et al, 2020). Using a rodent model, we also found that HMB could mitigate lipid metabolism disorders by reprogramming gut microbiota, as manifested by the increased ratio of Bacteroidetes to Firmicutes and elevated Bacteroidetesproduced propionic acid (Duan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic activity of the gut microbiota can be linked to host body energy homoeostasis by short-chain fatty acids (SCFAs), which are produced by gut microbiota catabolizing dietary fibers (Topping and Clifton, 2001). There is compelling evidence that nutrients can attenuate obesity by reprogramming gut microbiota (Xu et al, 2017;Yin et al, 2018;Zhang et al, 2019;Wang et al, 2020;Zhong et al, 2020). Using a rodent model, we also found that HMB could mitigate lipid metabolism disorders by reprogramming gut microbiota, as manifested by the increased ratio of Bacteroidetes to Firmicutes and elevated Bacteroidetesproduced propionic acid (Duan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nuciferine in lotus extracts is absorbed by the intestinal tract, showing a low permeability under a multi-component environment [ 81 , 82 ]. Nuciferine supplementation can prevent weight gain, reduce fat accumulation, and ameliorate lipid metabolic disorder in high-fat diet-fed rats [ 83 ]. Antibiotics substantially abolish the beneficial anti-hyperlipidemic and anti-liver steatosis effects of nuciferine.…”
Section: Potent Restoration Of Intestinal Microbiota-mediated Metabolic Syndromementioning
confidence: 99%
“…Antibiotics substantially abolish the beneficial anti-hyperlipidemic and anti-liver steatosis effects of nuciferine. 16S rRNA gene sequencing of fecal microbiota further shows that nuciferine also modulates gut microbiota dysbiosis and changes the diversity and composition of gut microbiota towards a healthy level in high-fat diet-fed rats [ 83 ]. The data from the composition of gut microbiota show that nuciferine significantly shifts microbial structure, which includes the reduction in the abundance of Butyricimonas and the enhancement of the abundance of Akkermansia, an anti-obesity bacterium in high-fat diet-fed animals [ 84 , 85 ].…”
Section: Potent Restoration Of Intestinal Microbiota-mediated Metabolic Syndromementioning
confidence: 99%
“…Numerous environmental factors may regulate tight junction protein and intestinal permeability, such as luminal microbiota, pro-inflammatory mediators and dietary component (3,4). High fat diet (HFD) induced obesity increased intestinal permeability came from animal models (5)(6)(7). The increased intestinal permeability was correlated with disrupted composition of gut microbiota (8).…”
Section: Introductionmentioning
confidence: 99%